2018
DOI: 10.14210/jcthink.v2.n1.p23
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review on relationships between Computational Thinking and Mathematics

Abstract: INTRODUCTION:A better understanding of the relationships between Computational Thinking and disciplines already present in the school curriculum may help the identification of possible educational benefits. This is particularly relevant in the case of Mathematics, which is a subject that constitutes itself as a hurdle to students in many Latin-American countries. OBJECTIVE: Identify and analyze didactic activities related to Computational Thinking and Mathematics reported in the literature regarding the target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 14 publications
1
23
0
1
Order By: Relevance
“…Many studies on CT in mathematics education focus on the content of geometry (Barcelos et al, 2018). This study also showed that there is potential to stimulate CT in this topic.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Many studies on CT in mathematics education focus on the content of geometry (Barcelos et al, 2018). This study also showed that there is potential to stimulate CT in this topic.…”
Section: Discussionsupporting
confidence: 54%
“…The term CT is closely related to the notion of problem solving (Selby & Woollard, 2013), where CT is primarily concerned with activities such as abstraction and decomposition to solve problems (Barcelos et al, 2018;Wing, 2006). In problem solving in mathematics, Polya (2004) writes that abstraction and problem decomposition are crucial for successful problem solving.…”
Section: Definition and Framework: Computational Thinkingmentioning
confidence: 99%
See 2 more Smart Citations
“…While many systematic reviews have been conducted on CT, very few systematic reviews have focused specifically on CT integration in STEM learning. Barcelos et al (2018) reviewed studies about learning mathematics through CT activities, finding CT has been implemented with diverse populations of students including elementary, middle, high school, undergraduate, graduate students, and teachers, and a variety of math skills and content was integrated with CT activities, including Euclidean geometry, algebra, arithmetic, math modeling, calculus, etc.…”
Section: Prior Systematic Reviews and Meta-analysismentioning
confidence: 99%